Loan to a bank under a credit agreement with a certificate of title as collateral - Ismayani, Ismayani (Journal of Law Science, 2025)
This research aims to analyse the problems arising in the granting of credit by PT Bank Sumut related to the inclusion of standard clauses in credit agreements that are detrimental to the debtor, in this case Rudi Hartono Silitonga. The case studied involves the provision of a credit facility with the type of KRK-SPK credit worth Rp. 4,500,000,000,- for financing the construction project of Bridge II Sta 0+815-Sta 0+835 (Sigalang-galang II Bridge) in Siantar Martoba District, Pematangsiantar City, which is guaranteed by a Certificate of Ownership (SHM) in the name of Irwan Nasution. The problems that arise are related to violations of the legal provisions governing the inclusion of standard clauses in credit agreements, which are allegedly not transparent and not in accordance with applicable consumer protection provisions. This research uses a normative legal approach to analyse the relevant laws and regulations as well as the credit agreement made unilaterally by the bank. The results showed that the standard clause in the credit agreement used by PT Bank Sumut had the potential to harm the debtor because there was no information disclosure regarding the transfer of obligations and conditions governing the transfer of insurance responsibility. In addition, arrangements regarding the transfer of credit risk are not adequately informed to the debtor, which leads to alleged violations of consumer rights. This research suggests the need for greater transparency in the preparation of clauses in credit agreements and the importance of better fulfilment of legal obligations by lenders to avoid harm to consumers